FRAMING VALUES: A DISCOURSE STUDY OF PANCASILA INTERNALIZATION IN PROJECT-BASED LEARNING - Silalahi, Maysarah; Wuriyani, Elly Prihasti; Gafari, M. Oky Fardian (Journal of Pragmatics and Discourse Research, 2025)
This study explores the development and implementation of a project-based assessment module aimed atstrengthening the Pancasila Learner Profile in Junior High School education. Beyond assessing pedagogicaloutcomes, the study integrates a discourse analysis lens to examine how Pancasila values are constructed,communicated, and internalized through classroom interaction and project-based dialogue. Using qualitativemethodsinterviews, observations, and document analysisthe study identifies discursive patterns in teacherguidance, student collaboration, and reflection activities. Findings reveal that project-based learning not onlyenhances critical thinking, collaboration, and value comprehension but also generates meaningful discourse thatreflects national identity and ethical reasoning. Teachers use specific language strategies to frame values such asmutual cooperation (gotong royong), diversity, and independence, often through narrative reflection andevaluative commentary. Meanwhile, student project presentations and written reflections show evidence oflinguistic shifts, metaphor use, and personalized value articulation. The assessment rubrics provided in the modulefurther shape the discourse around civic responsibility and ethical engagement. By foregrounding thecommunicative aspects of learning, this study highlights that value formation is not only behavioral but alsodiscursive. The implications suggest that project-based assessment can serve as both a pedagogical tool and adiscourse environment where students learn to articulate and negotiate values in context. The study recommendsfurther investigation into how educational discourse shapes identity, civic morality, and interculturalunderstanding in diverse Indonesian classrooms.